Rancang Bangun Alat Kendali Pengairan Perkebunan Selada Menggunakan Sensor Pengukur Debit Air Berbasis Mikrokontroler - Akbar Tegar Alam; Yoga Listi Prambodo (Sistem Komputer & Teknologi Intelegensi Artifisial (SIKOMTIA), 2022)
The irrigation controller in lettuce plantation irrigation aims to optimize the water that enters the ditches around the lettuce plantations so that the lettuce plants are not easily damaged due to stagnant water during the rainy season which can result in crop failure. Using the literature study method, collect data from sources that are relevant to the topic of the problem which is the main cause of crop failure in lettuce. From the existing conditions, it is necessary to design a tool to be able to minimize the water discharge to overcome the problems that occur. Schematics on the design and workings of the device were obtained from field observations and designed in the form of a prototype and similar to the logic of the tool when it works. The instrument was instructed as a control for the tool to measure the water discharge equivalent to the need in the ditches around the lettuce plants and the tool tested applied voltage measurements when the tool performed at time intervals that matched the initial requirements. The results of the research applied to the tool can work automatically and maintain the stability of the distribution of power to each sensor used with test intervals according to the results of the needs of lettuce plantation farmers.